RELATIONSHIP BETWEEN SLEEP HABITS AND SLEEP DISORDERS FOR 1-3 YEARS OLD CHILDREN AT POSYANDU LAWEN, PANDANARUM (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Sleep is a basic need that is very important for humans, especially at the age of children to support the achievement of optimal growth and development. However, the age of children is the age where a person often experiences sleep disturbances. External factors in the form of sleeping habits such as the application of children's sleeping hours, the use of shady lights when sleeping at night, and the use of electronic goods can cause sleep disturbances in children. Therefore, this study is aimed to describe the incidence of sleep disorders and to determine the relationship between sleep habits and sleep disorders in children aged 1-3. This research used an observational analytic study with a cross sectional design. The sample used was selected based on inclusion criteria with 55 consecutive sampling. Data were collected using the guided interview method and children's sleep disturbances were measured using the Brief Screening Infant Sleep Questionnaire (BISQ) form. Children aged 1-3 years who experience sleep disorders were 36.4%. Based on the bivariate test, there was no significant relationship between the application of sleeping hours and children's sleep disorders (p-value = 0.102 ), there was a significant relationship between the use of shady lights when sleeping at night with children's sleep disorders (p-value = 0.010), and there was a significant relationship between the use of electronic goods before bed with sleep disturbances in children (p-value = 0.004). This study shows that there is no relationship between the application of sleeping hours and children's sleep disorders. However, use of shady lights at night and the use of electronic goods before bed have a relationship with children's sleep disorders.
Keywords: sleep habits; sleep disorders; brief screening infant sleep questionnaire